Synthesis, Characterization and Activity Test of Natural Zirconium Zeolite (Zr-ZA) Catalyst in The Esterification Reaction of Glycerol with Acetic Acid Anhydride - Didik Krisdiyanto; Tutik Farihah; Hikmah Supriyati (Biology, Medicine, & Natural Product Chemistry, 2023)
Synthesis of Zr-ZA catalystused as catalyst for esterification reaction of glycerol with acetic acid anhydrous has been done. Catalysts are characterized using an infrared spectrophotometer, X-ray diffraction, and measurement of surface acidity, while reaction products are characterized using a gas chromatography-mass spectrometer. Effect of catalyst acidity, reaction time and re-addition of acetic acid anhydrous studied by glycerol conversion and selectivity value of triacetin were yielded. Infra-red spectrophotometer and X-ray diffraction analysis of the catalyst showed that the synthesized catalyst was zirconium zeolite (Zr-ZA), while esterification analysis using a gas chromatography-mass spectrometer showed a triacetin product.